The Integration of Farmers and Nomads: Archaeological Evidence for the Human Subsistence Strategy in Northwestern China during the Han Dynasty. (26th June 2020) - LI, Xin; LU, Minxia; CUI, Yifu; LIU, Ruiliang; MA, Minmin
Abstract : Abstract: The integration of farmers and nomads in northwestern China during the Han Dynasty (206 BCE ~ 220 CE) provides a crucial opportunity to reconstruct the material exchanges, formation and development of the Silk Road in antiquity. The subsistence strategy is arguably an effective proxy for the integration of various groups of people (e.g. farmers and nomads). In this paper, we have reported new stable isotope data from the Huangwan tombs dated to the Han dynasty in middle Gansu, which was the key juncture between the Han and Xiongnu empire, in order to fill the gap and further understand the substance strategies employed by the local people. According to the results of plant remains and stable isotopic data, millet farming, the typical agricultural activities for the Han Chinese in the Central Plains, was also the primary lifestyle for the Huangwan people in the mid Gansu. More importantly, this shows fundamentally remarkable difference from the agricultural practices in the Bronze Age Gansu Corridor, which were based on a variety of crops, including wheat, barley and millet. This major shift in the subsistence production at Huangwan can be correlated to a wider historical background in which the Han empire showed increasing political and military presence in the Gansu Corridor, indicating that local indigenous nomads followed the lifestyle of Han Chinese (e.g., millet farming), and/or the Han immigrates maintained millet farming.